An alternative approach to lie groups and geometric structures - Ortaçgil, Ercüment H. (Oxford University Press, 2018)
The theory of Lie groups is one of the most important mathematical themes of the last century and belongs to the centre of modern differential geometry. Whilst the subject is well established, this book aims to be the first to approach geometric theory of Lie groups from a new perspective.